Knowledge, Attitude and Practice of Health Care Professionals towards Antimicrobial Resistance and its stewardship at tertiary care teaching Hospital - Laxmi Shrestha; Sabitri Pokhrel; Amit Kumar Shrivastava; Buddhi Raj Pokhrel; Bishal Joshi; Pradip Chhetri (Journal of Karnali Academy of Health Sciences, 2021)
Background: Irrational antibiotic use leads to resistance, a serious problem which is increasing tremendously and requires urgent response. The goal of this study is to evaluate knowledge, attitude, and practice of health care professionals (HCPs) regarding antimicrobial resistance (AMR) and its stewardship.